Target Advertising and Market Transparency - Torben Stühmeier (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
This paper examines the effects of increased transparency over online news sources, e.g. due to news aggregators, on online news outlets and the advertising industry. The role of news aggregators is controversially discussed, where the discussion widely points on user side effect. The present paper widens the discussion on the advertising side and shows that aggregators can help to better target advertising messages to a more homogenous group of users and, in turn, may both benefit advertisers and news outlets.
Keywords: L22; L82; L86; 330